The Evaluation Of English Textbook Entitled Bahasa Inggris For The Tenth Year Of Vocational High School Published By Yrama Widya Based On The 2013 Curriculum - Dewi, Dyah Septiani Maha, Drs. Djoko Srijono, M.Hum, Dr. Dwi Haryanti, M.Hum (2014)
The objectives of the study are to describe the parts of the English textbooks that follow the guideline of the 2013 curriculum and to describe the parts of the English textbooks that do not follow the guideline of the 2013 curriculum. This research uses descriptive research. Documentation is method to collect the data, there are five steps to collect the data, namely: readingand understanding the contents, compairing the contents of the textbook with the 2013 curriculum,collecting the materials in the English textbook that follow and do not follow the guideline of the 2013 curriculum, analyzing the data which are found in the data source, and drawing conclusion. The result of this study show that they are five several points that used observing, questioning, associating, experimenting and networking. Parts of the English textbooks follow the guideline of the 2013 curriculum. The first is observing activity in all units especially in certain activity related on the picture observation. The second is questioning activity are certain activities where student must do. By the guideline of the teacher they must be able and brave to ask about everything related in the material. The third is In associating activity is appears in certain activity related with listening and speaking activity. The forth is experimenting activity is appears in every units in speaking activity focused on role play. The five is networking activity are certain activity related with writing and summary. Based on the result of analysis above, that they can find and use the right found that Englishtextbooks 99% followed guideline of the 2013 curriculum, except in point 4 (core competence) there are no point related with comprehend the meaning of song at 4.16.